Rendahnya asupan zat besi dan kepatuhan mengonsumsi tablet besi berhubungan dengan kejadian anemia pada ibu hamil di Wilayah Kerja Puskesmas I Kembaran, Banyumas - Ari Purwoko Widji Utomo; Detty Siti Nurdiati; Retna Siwi Padmawati (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2015)
ABSTRACTBackground: One of the nutritional problems that frequently occur in pregnant women is anemia, which is the biggest problem of micronutrient and the most difficult to overcome in the world. Anemia occurs at all stages of the life cycle, more commonly attacked pregnant women and children. The cause of anemiais iron deficiency which is needed to the formation of a hemoglobin (Hb). Deficiency of iron in the body is due to lack of consumption of food sources of iron and the non-compliance of pregnant women in consuming iron tablets. Supplementation of iron tablets and improvement of nutrient intake especiallygood source of iron is one of anemia prevention that has been done.Objectives: To determine the relationship between nutrient intake and the level of compliance in consuming iron tablets with incidence of anemia in pregnant women at work area of Puskesmas I Kembaran Banyumas.Methods: This was an observational study (survey) with a cross sectional design with 50 subjects of the third trimester pregnant women. The research used both quantitative and qualitative approaches.Results: The percentage of anemia in pregnant women in this study was 56.0%. The results of the multivariable analysis showed that only compliance-related iron tablets consumption significantly had relationship (p=0.001, RP=3.7, 95% CI:2.06-6.82) with the incidence of anemia in pregnant women. The high cost of animal food sources, the limitation of animal food sources diversity, and the dislike animal food sources consumption caused pregnant women choosing plant-based foods that where cheap and easily obtainable.Conclusions: This study proved that the intake of nutrients, especially iron and compliance of pregnant women in consuming iron tablets was still be the cause of anemia in pregnant women. Therefore, it needs to reduce and prevent maternal anemia by increasing the diversity of the consumption of iron foodsources, awareness of pregnant women to consume iron tablets, and the role of husband in encouraging pregnant women to consume iron tablets.KEYWORDS: anemia, compliance in consuming iron tablets, nutrient intakeABSTRAKLatar belakang: Salah satu masalah gizi yang banyak terjadi pada ibu hamil adalah anemia gizi, yang merupakan masalah gizi mikro terbesar dan tersulit diatasi di seluruh dunia. Hasil Riskesdas tahun 2010 menunjukkan 80,7% wanita usia subur (WUS) yang hamil mendapat/membeli tablet besi, namun sebagianbesar diketahui tidak patuh mengonsumsinya. Kekurangan besi dalam tubuh disebabkan kurangnya konsumsi makanan sumber zat besi dan ketidakpatuhan ibu hamil mengonsumsi tablet besi. Suplementasi tablet besi dan perbaikan asupan zat gizi terutama sumber zat besi merupakan upaya penanggulangananemia yang banyak dilakukan.Tujuan: Mengetahui hubungan asupan zat gizi dan tingkat kepatuhan mengonsumsi tablet besi dengan kejadian anemia pada ibu hamil di Wilayah Kerja Puskesmas I Kembaran Kabupaten Banyumas.Metode: Penelitian ini merupakan penelitian observasional (survey) dengan rancangan cross sectional dengan subjek penelitian 50 ibu hamil trimester III. Penelitian menggunakan pendekatan kuantitatif dan kualitatif.Hasil: Persentase anemia pada ibu hamil sebesar 56,0%. Hasil analisis multivariat hanya kepatuhan mengonsumsi tablet besi yang berhubungan bermakna (p=0,001, RP=3,7; 95% CI:2,06-6,82) dengan kejadian anemia pada ibu hamil. Harga sumber makanan hewani yang mahal, keanekaragaman sumber makanan hewani yang terbatas, dan ketidaksukaan mengonsumsi sumber makanan hewani menyebabkan ibu hamil memilih sumber makanan nabati yang murah dan mudah didapat.Kesimpulan: Asupan zat gizi terutama zat besi dan kepatuhan ibu hamil mengonsumsi tablet besi masih menjadi penyebab anemia pada ibu hamil. Oleh sebab itu, perlu dilakukan upaya penanggulangan dan pencegahan anemia ibu hamil dengan cara peningkatan keanekaragaman konsumsi bahan makanan sumber zat besi, kesadaran ibu hamil untuk mengonsumsi tablet besi, dan peran serta suami dalam mendorong ibu hamil mengonsumsi tablet besi.KATA KUNCI: anemia, kepatuhan minum tablet besi, asupan zat gizi